Strategy For Improving Employee Performance Through Job Characteristics Strengthening Program, Empowerment & Work Motivation (Empirical Study On Chemical Industry Employees In Bogor Regency) - Riza Aditriawan Anggorodi; Hari Gursida; Widodo Sunaryo (PT. INOVASI TEKNOLOGI KOMPUTER, 2025)
This study aims to analyze the influence of job characteristics and empowerment on employee performance, with work motivation as an intervening variable, among employees in the chemical industry in Bogor Regency. The method used is a mixed methods approach, namely quantitative through questionnaires and qualitative through interviews with employees at PT. RDA Reindo Dinamika, PT. Mulia Agung, and PT. Kimia Utama with a total sample of 232 respondents. The data analysis techniques used were path analysis and the Delphi technique. The results of the quantitative approach show that job characteristics and work motivation have a positive and significant impact on employee performance. Empowerment does not show a significant direct effect on performance, but it has a positive impact on work motivation. Work motivation acts as a mediator in the relationship between job characteristics and empowerment on employee performance. The qualitative approach reinforces the quantitative results, where employees express that aspects such as skill variety, autonomy, feedback, and job meaning can enhance work enthusiasm and quality. Empowerment that is not accompanied by effective communication and consistent management support tends to have less direct impact on performance improvement. Work motivation emerges as an important factor that strengthens the positive influence of the work environment on performance. Improvement of job characteristics and empowerment, when supported by high work motivation, can be an effective strategy in enhancing employee performance.